Impact Of Measurement Of Service Quality Using The Servqual Method: Case Study In Pt. Karya Mandiri Sepakat Surabaya - Achmad Daengs GS; Moch. Rizaldy Rahmansyah; Rina Dewi; Diana Zuhro; Indriana Kristiawati (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The research for this thesis takes the title: